PENGARUH PARTISIPASI MASYARAKAT DAN ETIKA LINGKUNGAN TERHADAP PEMBANGUNAN BERKELANJUTAN STUDI KASUS : KECAMATAN TEMBALANG - ristiana .; edi santosa; teguh yuwono (Journal of Politic and Government Studies, 2016)
In the theoretically, public has a strategic role in the development process. This community has the right and the obligation to participate in the development process. Public participation in sustainable development is set out in law No. 32 years 2009 about the environment have explained about the obligation, right and prohibition restriction outlined in section 65. In the article described that the public given space to participate in managing the environment. The public reserves the right reject or accept all the activities related to the environment. The public has the right to file an objection when construction is done negatively affect the living environment of the public.Research method used are mix method, namely the merger between quantitative methods and qualitatif method. Quantitative methods as main methods and quantitative methods as a method of supporting research that can not be axplained through quantitative. Reseacrh conducted at Tembalang by taking the sendangguwo village and tembalang village as research sample. Reseacrh intrument using a detailed questionnaire with 68 respondent and interview to related parties.The result of such research is the influence that low public participation and sustainable development. That is because the public is till tied to the government in the process of sustainable development. Enviromental ethics provide a pretty strong influence to sustainable development. It is because the government together with the public should really pay attention to the envoronment so that the construction can be done in a sutainable way without reducing the quality of the environment.The advice given is to make government more angaging the public in the process of sustainable development and the goverment togethet with the public should pay more attention to the environment in every development in order not to reduce the quality of the environment.Key : Influence, Public Participation, enviromental ethic and sustainable development